Implementasi Sustainable Development Goals (SDGs) dalam Meningkatkan Kepuasan Masyarakat di Provinsi Banten - Bahtiar Effendi (Universitas Matana, 2021)
This study aims to analyze the factors that influence community satisfaction related to the implementation of the Sustainable Development Goals (SDGs) through economic performance, social performance, and environmental performance in Banten Province. This study uses questionnaire data given to respondents in Cilegon City. Data analysis was performed by multiple regression analysis. The findings obtained are that economic performance has a significant positive effect on community satisfaction with a significance level below 5% or 0.05 i.e. = 0.001 and social performance has an insignificant positive effect on community satisfaction with a significance level above 5% or 0, 05, namely = 0.721 and environmental performance has a significant positive effect on community satisfaction with a significance level below 5% or 0.05, namely = 0.009. Furthermore, the implementation of the SDGs program simultaneously through economic performance, social performance and environmental performance has been proven to have a significant positive effect on community satisfaction with a significance level below 5% or 0.05, namely = 0.000. The implication of this research is that the company is expected to further increase community involvement and supervise the implementation of the SDGs program that has been planned by the company.